Avaliação hemostática de jovens mulheres usuárias ou não de contraceptivos orais combinados e dispositivos intrauterinos com liberação de levonorgestrel por meio do teste de geração de trombina e dímero D. - Ana Paula de Jesus Souza (2024)
Several genetic and non-genetic factors can favor a hypercoagulable state that, not infrequently, evolves into a thrombotic event. Among non-genetic factors, the use of oral contraceptives (OCs) has been associated with activation of the hemostatic system because they have hormones in their formulation. No entanto, o uso do dispositivo intrauterino (DIU) com liberação de levonorgestrel não parece ter efeito pró-trombótico. Therefore, it is important to carry out new studies using this approach, as well as the search for new diagnostic tools that assist in the diagnosis of hypercoagulability in various diseases and clinical conditions, and in the risk assessment of such individuals. Therefore, in the present study, the thrombin generation technique (TGT) was used in such an important context of women's health represented by contraception methods, whether the use of OCs or an intrauterine device (IUD). Although very promising, TGT is still little known and used in Brazil. Given the above and considering the frequency of use of OCs and IUDs by a large contingent of women of childbearing age, the present study aimed to evaluate the hemostatic profile of young women using OCs or not (controls) or IUDs with levonorgestrel release. The study included 100 young, healthy women, aged between 18 and 40 years, most of them students at the Federal University of Minas Gerais (UFMG) distributed in 3 (three) subgroups: users of IUDs (n=24) or OCs (n= 39) and, also, those who did not use IUDs or OCs (n=37, controls). After approval of the project at CEP/UFMG and post-informed consent, blood samples were collected for laboratory analysis. TGT analyzes (CAT method) were performed using tissue factor (TF) in low and medium concentrations and reading on a fluorimeter coupled with the Thrombinoscope software. TGT parameters such as Lagtime, Endogenous Thrombin Potential (ETP), Peak, Time to Peak (ttP), Start Tail and Velocity Index were calculated using the above software. An increase in thrombin generation was observed in women using OCs compared to those using IUDs and controls. This finding can be explained by the possible increase in procoagulants and, also, a reduction in the components of natural anticoagulation (Protein C - PC, Protein S - PS, Antithrombin - AT and Inibiter of the Fator Tissular Via – TFPI). Our findings reinforce previous studies regarding the activation of the hemostatic system in young Brazilian women resulting from the use of OCs. At the same time, the data reaffirm the importance of continuing to seek the proper standardization and validation of the TGT, given its great potential for application to evaluate states of hypercoagulability, a gap that still exists in clinical laboratories.